Characterising health care‐associated bloodstream infections in public hospitals in Queensland, 2008–2012. Issue 7 (18th April 2016) - Si, Damin; Runnegar, Naomi; Marquess, John; Rajmokan, Mohana; Playford, Elliott G
Abstract: Objective: To describe the epidemiology and rates of all health care‐associated bloodstream infections (HA‐BSIs) and of specific HA‐BSI subsets in public hospitals in Queensland. Design and setting: Standardised HA‐BSI surveillance data were collected in 23 Queensland public hospitals, 2008–2012. Main outcome measures: HA‐BSIs were prospectively classified in terms of place of acquisition (inpatient, non‐inpatient); focus of infection (intravascular catheter‐associated, organ site focus, neutropenic sepsis, or unknown focus); and causative organisms. Inpatient HA‐BSI rates (per 10 000 patient‐days) were calculated. Results: There were 8092 HA‐BSIs and 9418 causative organisms reported. Inpatient HA‐BSIs accounted for 79% of all cases. The focus of infection in 2792 cases (35%) was an organ site, intravascular catheters in 2755 (34%; including 2240 central line catheters), neutropenic sepsis in 1063 (13%), and unknown in 1482 (18%). Five per cent (117 of 2240) of central line‐associated BSIs (CLABSIs) were attributable to intensive care units (ICUs). Eight groups of organisms provided 79% of causative agents: coagulase‐negative staphylococci (18%), Staphylococcus aureus (15%), Escherichia coli (11%), Pseudomonas species (9%), Klebsiella pneumoniae/oxytoca (8%), Enterococcus species (7%), Enterobacter species (6%), and Candida species (5%). The overall inpatient HA‐BSI rate was 6.0 per 10 000 patient‐days. The rates for important BSI subsets included: intravascular catheter‐associated BSIs, 1.9 per 10 000 patient‐days; S. aureus BSIs, 1.0 per 10 000 patient‐days; and methicillin‐resistant S. aureus BSIs, 0.3 per 10 000 patient‐days. Conclusions: The rate of HA‐BSIs in Queensland public hospitals is lower than reported by similar studies elsewhere. About one‐third of HA‐BSIs are attributable to intravascular catheters, predominantly central venous lines, but the vast majority of CLABSIs are contracted outside ICUs. Different sources of HA‐BSIs require different prevention strategies.